Evaluation of different agricultural residues as raw materials for pulp and paper production using a semichemical process. (10th July 2017) - Gonzalo, A.; Bimbela, F.; Sánchez, J.L.; Labidi, J.; Marín, F.; Arauzo, J.
Abstract: This work assesses six different agricultural residues with the aim of finding alternative raw materials for a soda semichemical pulping process: stems of bell and chili pepper ( Capsicum annuum ), broad bean ( Vicia faba ), asparagus ( Asparagus officinalis ), pea ( Pisum sativum ), and okra ( Abelmoschus esculentus ). Pulping yields higher than 60% (m/m) were obtained, except for pea stems (43%). The drainability of all the pulps, expressed as the Schopper-Riegler index (ºSR), had values of over 70 ºSR. The Kajaani analyses of the fibers showed acceptable fiber lengths in all cases (0.64–0.92 mm), but on average shorter than the lengths of pulps from a commercial fluting paper (Old corrugated Container, OCC), that was found to be 1.27 mm. Handsheets of paper were produced both with the pulps under study and with mixtures of these pulps with OCC pulp. Several properties were measured to assess the use of the new fibers in a paper for cardboard production. The property showing the greatest differences was the Gurley porosity, ranging from 25 mL/min (asparagus) to 1300 mL/min (broad bean). Of the six residues tested, the okra residue fiber showed better properties than the commercial paper fiber (Concora Medium Test indexes: 1.5 N m 2 /g and 1.1 N m 2 /g respectively, Burst Indexes: 2.3 kPa m 2 /g and 1.7 kPa m 2 /g, respectively), yielding similar mechanical properties to those of high quality fibers obtained from miscanthus ( Miscanthus giganteus ). Broad bean residue could also be a promising raw material, though its properties are not as good as okra's. Highlights: Six agricultural residues evaluated for producing pulps and papers by soda pulping. Pulps from two residues mixed with recovered fibers for producing packaging paper. Residues from broad bean and okra are promising feedstocks for manufacturing paper.